Energy‐maximising moment‐based constrained optimal control of ocean wave energy farms. Issue 14 (6th September 2021) - Faedo, Nicolás; Scarciotti, Giordano; Astolfi, Alessandro; Ringwood, John V.
Abstract: Successful commercialisation of wave energy technology inherently incorporates the concept of an array of wave energy converters (WECs). These devices, which constantly interact via hydrodynamic effects, require optimised control that can guarantee maximum energy extraction from incoming ocean waves while ensuring, at the same time, that any physical limitations associated with device and actuator systems are being consistently respected. This paper presents a moment‐based energy‐maximising optimal control framework for WECs arrays subject to state and input constraints. The authors develop a framework under which the objective function (and system variables) can be mapped to a finite‐dimensional tractable quadratic program (QP), which can be efficiently solved using state‐of‐the‐art solvers. Moreover, the authors show that this QP is always concave, i.e. existence and uniqueness of a globally optimal solution is guaranteed under this moment‐based framework. The performance of the proposed strategy is demonstrated through a case study, where (state and input constrained) energy‐maximisation for a WEC farm composed of CorPower‐like WEC devices is considered.